2009
DOI: 10.3113/fai.2009.0854
|View full text |Cite
|
Sign up to set email alerts
|

Triple Nerve Block at the Knee for Foot and Ankle Surgery Performed by the Surgeon: Difficulties and Efficiency

Abstract: We found triple nerve block at the knee to be a safe and reliable method of regional anesthesia providing low morbidity, high success rate, long acting analgesia, and fewer complications than general or spinal anesthesia. It is a simple method that can be performed by the orthopaedic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
12
1
3
Order By: Relevance
“…While uncommon, these include allergic reactions to the anesthetic agent, vascular damage at the injection site, mechanical damage to the nerve at the injection site, and the risk of intravascular injection or hematoma. 2,4,7,19 There were 6 complications in total, 4 in the single-catheter group and 2 in the dual-catheter group. Four of the complications were neuritic in nature, and there were 2 in each group; 2 of these patients had improvement in their symptoms with time.…”
Section: Discussionmentioning
confidence: 98%
“…While uncommon, these include allergic reactions to the anesthetic agent, vascular damage at the injection site, mechanical damage to the nerve at the injection site, and the risk of intravascular injection or hematoma. 2,4,7,19 There were 6 complications in total, 4 in the single-catheter group and 2 in the dual-catheter group. Four of the complications were neuritic in nature, and there were 2 in each group; 2 of these patients had improvement in their symptoms with time.…”
Section: Discussionmentioning
confidence: 98%
“…In orthopedic surgery, various anesthetic methods such as general, regional (epidural, spinal, intravenous, and peripheral nerve blocks) and local anesthesia are applied 1 , 2 , 3) . However, it has been reported that general or spinal anesthesia in lower extremity operation among advanced age patients lead to mortality in 15 of 10,000 patients and there is a possibility of various complications, such as postoperative pain, respiratory problems, headache, hypotension, and urinary retention 4) .…”
Section: Introductionmentioning
confidence: 99%
“…It is also an efficacious way for postoperative pain control and requires no fasting. Therefore, nerve block has acquired a larger role in orthopedic surgery 2 , 3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ankle, trauma of the sartorial branch due to arthroscopic portal placement has been reported (Ferkel et al, 1996). Blockade of this nerve combined with other nerves has also been done for ankle and foot surgery (Varitimidis et al, 2009). Therefore, knowledge of the anatomy of the sartorial branch is crucial to successful and safe surgical interventions.…”
Section: Introductionmentioning
confidence: 99%